Non-financial reporting pursuant to the SIN standard at the Warsaw Stock Exchange - Błażyńska, Joanna (Raportowanie według SIN na GPW w Warszawie, 2020)
The paper presents the results of research on the evaluation of Non-Financial Statements (Reports), drafted pursuant to the SIN standard (the Polish Non-Financial Information Standard) by a hypothetical investor. The research question was defined of whether the Non-Financial Statements (Reports), which — according to the declarations of the listed companies — are drafted in concordance with the SIN standard, fulfil the requirements set forth by the standard, and thus provide useful non-financial information for the interested parties. The research covered all reports fulfilling the indicated criterion, i.e. 20 listed companies. In the majority of cases, the research results indicate that there are considerable deviations from the SIN standard guidelines. There were five heterogeneity levels in the approach to the SIN standard. In order to carry out the goal, content analysis, descriptive and comparative analysis, as well as the induction method were employed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 7-18
Keywords: non-financial information; non-financial information standard; non-financial information reporting areas; SIN standard KPIs; informacje niefinansowe; standard informacji niefinansowych; obszary raportowania informacji niefinasowych; kluczowe wskaźniki SIN